Tailor-Made Surgery Based on Functional Networks for Intractable Epilepsy - Kamada, Kyousuke; Kapeller, Christoph; Takeuchi, Fumiya; Gruenwald, Johannes; Guger, Christoph (Frontiers in Neurology, 2020)
Normal and pathological networks related to seizure propagation have got attention to elucidate complex seizure semiology and contribute to diagnosis and surgical monitoring in epilepsy treatment. Since pathology of focal and generalized epileptogenic syndromes might involve multiple foci and large-scale networks, we applied high gamma activity (HGA) mapping, electrophysiolpgy (cortco-cortico evoked potential; CCEP) and tractography to make detailed diagnosis for complex syndrome. All 14 epilepsy patients with no or little abnormality on images investigations underwent subdural grid implantation for epilepsy diagnosis. To perform quick network analysis, we recorded and analyzed HGA of epileptogenic activity and CCEPs to identify pathological activity distribution and network connectivity. Pathological CCEPs showed 2 negative deflections consisting of early (less than 40 ms) and late (less than 150 ms) components in electrically stable circumstance at bed side and early CCEPs appeared in 57% of the patients. On the basis of the CCEP findings, tractography detected anatomical connections. Early components of pathological CCEPs diminished after complete disconnection of tractography-based fibers between the foci in 7 of 8 cases. One case with residual pathological CCEPs showed poorer outcome. Thirteen (92.8%) patients with or without CCEPs who underwent network surgery had favorable prognosis except for a case with wide traumatic epilepsy. Intraoperative CCEP measurements and HGA mapping enabled visualization of pathological networks and clinical impotence as a biomarker to improve functional prognosis. HGA/CCEP recording should shed light on pathological and complex propagation for epilepsy surgery.